Information Technology in Sports Clothing - M Iffan; M R Khoirul (International Journal of Research and Applied Technology (INJURATECH), 2021)
The purpose of this study, to meet the needs of Muslim women to carry out exercise activities so that Muslim women do not struggle to find clothes that fit their style in everyday life, using Social media as a tool for promotion. This study used a descriptive method to describe the efforts of Muslim women's sports clothing through social media as a promotional tool because nowadays many women who already use hijab during exercise. The results obtained from this research added employment opportunities. The reason to be accomplished and get noticed is the clarity of the utilization of social media and see what is being needed by women today. The conclusion of this research is young people especially those who have not opened the business, this business is used as an example or the first step of opening the daily effort to increase income and learn to become a professional entrepreneur